2022
DOI: 10.3390/biom12030405
|View full text |Cite
|
Sign up to set email alerts
|

A Series of PSMA-Targeted Near-Infrared Fluorescent Imaging Agents

Abstract: We have synthesized a series of 10 new, PSMA-targeted, near-infrared imaging agents intended for use in vivo for fluorescence-guided surgery (FGS). Compounds were synthesized from the commercially available amine-reactive active NHS ester of DyLight800. We altered the linker between the PSMA-targeting urea moiety and the fluorophore with a view to improve the pharmacokinetics. Chemical yields for the conjugates ranged from 51% to 86%. The Ki values ranged from 0.10 to 2.19 nM. Inclusion of an N-bromobenzyl sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…We observed significantly higher (p < 0.05) binding affinity and PSMA+ cell binding both in vitro and in vivo for new agents, specifically 177 Lu-Alb-L4 and 177 Lu-Alb-L5 (Structure B), compared to 177 Lu-Alb-L2 and 177 Lu-Alb-L3 (Structure A). 177 Lu-Alb-L6 displayed low binding affinity, likely due to the long PEG linker, as we noted earlier with a similar construct [34]. Proof-of-concept cell efficacy data further confirmed the effect of enhanced cellular uptake and internalization of 177 Lu-Alb-L5 (Structure B) compared to 177 Lu-L1 or 177 Lu-Alb-L2 (Structure A).…”
Section: Discussionsupporting
confidence: 78%
“…We observed significantly higher (p < 0.05) binding affinity and PSMA+ cell binding both in vitro and in vivo for new agents, specifically 177 Lu-Alb-L4 and 177 Lu-Alb-L5 (Structure B), compared to 177 Lu-Alb-L2 and 177 Lu-Alb-L3 (Structure A). 177 Lu-Alb-L6 displayed low binding affinity, likely due to the long PEG linker, as we noted earlier with a similar construct [34]. Proof-of-concept cell efficacy data further confirmed the effect of enhanced cellular uptake and internalization of 177 Lu-Alb-L5 (Structure B) compared to 177 Lu-L1 or 177 Lu-Alb-L2 (Structure A).…”
Section: Discussionsupporting
confidence: 78%
“…Kularatne et al designed and synthesized OTL78, which has a circulation half-life of 17 min and excellent TBR (5:1) for PSMA-targeted NIRF surgery 14 . Chen et al reported that PSMA-targeted NIRF dyes for PSMA FGS and DyLight800-10 achieved the highest uptake in PCa tumors 96 (Table 5 ). Furthermore, Yang et al conjugated an iridium(III) complex with the inhibitor Lys-urea-Glu to create a PSMA-targeted iridium(III) probe 97 .…”
Section: Psma-fgsmentioning
confidence: 99%